Factors influencing the intention of kedayan muslims to perform the traditional culture associated with syncretism - Mohd Mokhtar, Ros Aiza; Khalek, Aiedah Abdul; Sa'ari, Che Zarrina; Mohad, Abd Hakim (Universiti Putra Malaysia, 2018)
In the study of religion, syncretism has been conveyed as a controversial concept and has become an issue for debate because it depicts ‘impurity’ or ‘inauthenticity’. The term has been widely used by some Western scholars to elaborate on its practice among Ancient and Christian societies, and at the same time, it is also used in the context of Muslim communities, particularly in describing the practice of traditional cultures in Malaysia that were rejected by Muslim reformers. In practice, however, traditional culture cannot be easily distinguished from Muslim practices. Thus, what explains the desire of some Muslims to continue practising elements of their traditional culture associated with syncretism? This paper aims to discover the factors influencing the intention of the Kedayan people to practise elements their traditional culture that are associated with syncretism. Data were self-administered among 414 respondents and analysed using descriptive and inferential analyses of the Statistical Package for the Social Sciences. The results of this study revealed that the Kedayan people have a tendency to continue with practices of their traditional culture that may still contain remnants of syncretism. In addition, the results also revealed their agreement with the common perception of traditional culture and subjective norms as factors influencing Kedayans’ intention to practise their traditional culture.